Challenges and opportunities for implementing digital health interventions in Nepal: A rapid review - Parajuli, Rojina; Bohara, Dipak; KC, Malati; Shanmuganathan, Selvanaayagam; Mistry, Sabuj Kanti; Yadav, Uday Narayan (Frontiers in Digital Health, 2022)
Background In recent times, the use of digital technologies in healthcare has been well recognized in Nepal. It is crucial to understand what is working well and areas that need improvements in the digital health ecosystem. This narrative review was carried out to provide an overview of the challenges and opportunities for implementing digital health interventions in Nepal. We followed the PRISMA guidelines and used various search terminologies such as telehealth, telemedicine, e-health, mobile health, digital health, and Nepal to identify primary studies published between 1st January 2010 to 30th December 2021 in four databases, namely PubMed, Google Scholar, Scopus, and CINAHL. Initially identified studies were screened against predetermined selection criteria, data extraction from the included studies was done independently by three authors. The review identified various challenges, opportunities, and benefits for implementing digital health initiatives in Nepal. The most expressed challenge was inadequate technical facilities (lack of electricity and internet) and difficult geographical distribution, which makes transportation difficult in hilly areas. Lack of skilled manpower and lack of supportive policies were also notable challenges documented. Meanwhile, major opportunities identified were education and training of the students and health practitioners as well as increasing awareness among general population. The study identified various factors that can be associated with successful implementation of digital health initiatives in Nepal. Our findings may guide to formulation of digital health policy and interventions to improve mass health outcomes using digital health services.